1990
DOI: 10.2514/3.23261
|View full text |Cite
|
Sign up to set email alerts
|

Turbine blading designed for high heat load space propulsion applications

Abstract: The operating conditions and the propellant transport properties used in Earth-to-orbit (ETO) applications affect the aerothermodynamic design of ETO turbomachinery in a number of ways. This paper discusses some aerodynamic and heat-transfer implications of the low molecular weight fluids and high Reynolds number operating conditions on future ETO turbomachinery. The objective of this work was to examine turbine blading concepts for increasing life and reliability by reducing thermal heat load. Using the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Arts et al (1997), Dunn et al (1994), and Blair (1994) among others, showed midspan rotor blade leading edge heat transfer rates nearly twice the highest values seen elsewhere on the blade. Civinskas et al (1990) showed heat transfer in this region was reduced using a large leading edge diameter, and aerodynamic losses were not significantly increased. The rotor shape was chosen to achieve acceptable aerodynamics with a lower than typical ratio of peak-to-average heat transfer.…”
Section: Fig 1 Transonic Turbine Blade Cascadementioning
confidence: 94%
“…Arts et al (1997), Dunn et al (1994), and Blair (1994) among others, showed midspan rotor blade leading edge heat transfer rates nearly twice the highest values seen elsewhere on the blade. Civinskas et al (1990) showed heat transfer in this region was reduced using a large leading edge diameter, and aerodynamic losses were not significantly increased. The rotor shape was chosen to achieve acceptable aerodynamics with a lower than typical ratio of peak-to-average heat transfer.…”
Section: Fig 1 Transonic Turbine Blade Cascadementioning
confidence: 94%
“…Additional information regarding the tests was given by Hudson, Gaddis, Johnson, and Boynton(1991), Table I lists some of the flow and relevant geometric characteristics of this turbine at the design point. Further details of the geometry are given by Civinskas, Boyle, and McConnaughey(1990). The analysis was done using the mass flow at the design point pressure ratio for various wheel speeds.…”
Section: Resultsmentioning
confidence: 99%